2013
DOI: 10.1101/gad.214023.113
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of the corepressors NCoR1 and SMRT in homeostasis

Abstract: Epigenetic regulation of gene expression is strongly influenced by the accessibility of nucleosomal DNA or the state of chromatin compaction. In this context, coregulators, including both coactivators and corepressors, are pivotal intermediates that bridge chromatinmodifying enzymes and transcription factors. NCoR1 (nuclear receptor corepressor) and SMRT (silencing mediator of retinoic acid and thyroid hormone receptor) are among the best-characterized corepressors from a molecular point of view. These coregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
295
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(307 citation statements)
references
References 122 publications
10
295
0
2
Order By: Relevance
“…PRDM16, which is involved in differentiation of brown adipose tissue [31] and stem cell maintenance [32], was hypermethylated on six CpG sites. NCOR2, a co-repressor of importance for homeostatic processes, inflammation and circadian rhythms [33], had five hypermethylated CpGs and one hypomethylated CpG. We then assessed the presence of regions of vulnerability to methylation across the whole genome.…”
Section: Resultsmentioning
confidence: 99%
“…PRDM16, which is involved in differentiation of brown adipose tissue [31] and stem cell maintenance [32], was hypermethylated on six CpG sites. NCOR2, a co-repressor of importance for homeostatic processes, inflammation and circadian rhythms [33], had five hypermethylated CpGs and one hypomethylated CpG. We then assessed the presence of regions of vulnerability to methylation across the whole genome.…”
Section: Resultsmentioning
confidence: 99%
“…We also have shown that, in contrast with the native receptor, TRÎČ mutants unable to bind the corepressor cannot antagonize Ras-mediated transformation and tumorigenesis (26), reinforcing the idea that NCoR is an essential mediator of the tumor-suppressive actions of TRÎČ. TRÎČ-mediated up-regulation of NCoR could extend the scope of genes that are influenced by the receptor, because the corepressor has been shown to repress transcription through other nuclear receptors and numerous transcription factors with a role in cancer progression (1,12). Therefore, repression of prometastatic gene expression could be a consequence of NCoR interaction with this receptor or, more likely, with other transcription factors that associate with their promoters.…”
Section: Discussionmentioning
confidence: 99%
“…As expected from their prevalent role in integrating the action of many transcription factors, NCoR and HDAC3 affect numerous developmental and homeostatic processes (12). In addition, there is increasing evidence that NCoR could play a significant role in cancer.…”
mentioning
confidence: 99%
“…In the absence of ligand, some NRs, such as the thyroid hormone receptor (THR) and retinoic acid receptor, repress gene expression by interacting with transcription corepressors including nuclear receptor corepressor 1 (NCoR1) and silencing mediator of retinoid and thyroid receptors (SMRT) (24); binding of NR antagonists can also lead to corepressor recruitment (25). Both NCoR1 and SMRT are large (ÏŸ250 kDa) pro-teins that bind histone deacetylase complexes and contain multiple NR interaction domains at their C termini (26). Interaction domain motifs are composed of short amphipathic helices with an I/LXXI/VIXXXL/F/Y consensus that associate with NRs by binding to a hydrophobic cleft on the LBD (27).…”
mentioning
confidence: 99%